Early synaptic dysfunction of striatal parvalbumin interneurons in a mouse model of Parkinson’s disease - Quansheng He; Xiaowen Zhang; Hongyu Yang; Dahui Wang; Yousheng Shu; Xuan Wang (iScience)
Summary: In Parkinson’s disease (PD), the loss of dopaminergic signaling remodels striatal circuits, causing abnormal network activity. The timing and impact on various striatal cell types during this reorganization are unclear. Here we demonstrate that dopamine depletion rapidly reduces parvalbumin (PV) expression. At the synaptic input level, PV interneurons shift toward inhibition in the excitation-inhibition balance early on, a week before a similar shift in spiny projection neurons (SPNs). At the cellular level, both PV interneurons and SPNs experience a significant decrease in their spiking and bursting rates, respectively, which corresponds to a reduction in gamma and beta (early beta) oscillations during the early stage of PD. Importantly, the pharmacogenetic activation of PV interneurons reverses gamma deficits and suppresses beta (late beta) oscillation in the striatum of parkinsonian mice. Collectively, our findings underscore the vulnerability of PV interneurons to dopamine depletion and their responsibility for the evolution of abnormal activities in parkinsonian striatum.